Pengembangan Sosis Gasuhiru Berbasis Pangan Lokal Ikan Gabus “Tokok” Dan Tepung Komposit Terhadap Sifat Organoleptik, Kadar Zat Gizi Dan Daya Terima Sosis Gasuhiru - Dwiaulia Khusnul Khotimah; Abdul Salam; AASP Chandradewi; Irianto Irianto (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background. Nutrition less in infants is a health problem around the world especially the countries develop. In Indonesia nutritional problems less in toddlers about 19.6%. Nutritional problems have little effect on the low quality of human resources, especially the impact of toddlers who are malnourished by poor brain development, unoptimal physical growth, and metabolic developments (the Kemenkes RI, 2014). The current state of nutrition especially in children is still ematitiate. Given the impact of the nutrient less widespread, it is necessary to do a handling of PMT in the form of sausages using local food that is effective in increasing the weight of children with less nutritional nutrition.Metodelogi. In this study used experimental research Desan with a complete random draft (RAL) One treatment comparison of cork fish with composite flour 75%: 25% 80%: 20% 85%: 15%. Data processing. Processing of data obtained from observations presented in the form of tables, to find out the nature of organoleptic (aroma, flavor, texture and color) in each addition of the sausage making materials processed and analyzed using a statistical analysis of One Way Anova at a trust level of 95% (A = 0.05). If there is a significant impact, the data is analyzed further using the Tukey test to see which treatment is causing the difference. Research results. The comparison of cork fish and composite flour is significant effect on the taste color of texture and aroma. The PMT of Gasuhiru sausage contains 262KKL and 16.72 gr of protein in 100gr. Gasuhiru sausage receiving 83.3% well received.Conclusion: The most liked sausage is a comparison of 85%: 15%. The administration of PMT provides a significant effect on children's weight loss and is 3 times greater than the Conntrol group.